Mobile Phone-Based Health Reminders on Treatment of Tuberculosis Patient Relapse - Djuma, Elviera; Hariyati, Rr. Tutik Sri; ., Masfuri (Jurnal Ilmiah Perawat Manado (Juiperdo), 2023)
Abstract Background: Treatment nonadherence is multifaceted, complex, and a significant barrier to TB control and contributes to the spread of disease and death. Mobile phone-based strategies have been used in programs to increase the adherence of tuberculosis patients to taking medication. Objective: To determine the effectiveness of using cell phone-based health reminders on the adherence of tuberculosis patients to treating their disease. Methods: An online database of academic journals is used with a literature review method using the keywords "mobile phone-based health reminders," "tuberculosis," "adherence," and "treatment." Results: The use of cell phone-based health reminders on the treatment adherence of tuberculosis patients was found to provide convenience and benefits in providing health services. Patients and health workers seek and provide good services so that they can encourage and support TB patients to take medication. Conclusion: Cell phone-based health reminders provide great benefits in controlling the treatment of patients with relapsed tuberculosis.